PENINGKATAN KAPASITAS PRODUKSI DAN BRANDING CAMILAN COKLAT CHIPS PADA BEEMA BROWNIES - Wijaya ADH, IGKG Puritan; Yusadara, I Gede Putra Mas; Wirawan, I Wayan Arik; Wikranta Arsa, I Gusti Ngurah; Saputra, I Made Arya Budhi; Gautama, I Made Bhaskara; Sari, Ni Made Wirastika; Rini, Erma Sulistyo; Parwita, I Made Mika; Damayanthi, Ni Putu Desy (Jurnal Berdaya Mandiri, 2024)
BEEMA Brownies, a snack manufacturer, has started producing snacks in the form of Brownies-flavored Choco Chips and several other flavors made from good quality ingredients without artificial sweeteners and preservatives. Even though in the middle of a pandemic, we are still optimistic that we can capture a sufficient consumer market because the market need for healthy snacks is still very much needed. With the implementation of Phase 1 activities, namely the provision of production equipment, namely ovens, product packaging tools and 2 sets of baking sheet equipment, the current production capacity of Beema Brownies has increased from a maximum of 150/package per day with an average product requirement of around 100-200 packs/sold. day to 300/pack per day using the 2 ovens that you already have. Training on the use of the equipment provided has also been carried out so that BEEMA production employees are able to use the newly provided oven equipment and packaging equipment. The amount of production has been able to meet the average demand every day. BEEMA Chocochips has also increased the HR capabilities of 2 employees who help produce in an effort to increase the amount of Chocochips production. By having a website for UKM BEEMA Chocchips, they already have the means for digital identity and digital promotional content for their products so that they are known to the wider community. Keywords: Brownies, Production, Website